Part 1, executed electronic state decomposition of energetic molecules. Part 2, conformation specific reactivity of radical cation intermediates of bioactive molecules - Bhattacharya, Atanu, author; Bernstein, Elliot R., advisor; Levinger, Nancy E., committee member; Van Orden, Alan K., committee member; Szamel, Grzegorz, committee member; Bartels, Randy A., committee member (Colorado State University. Libraries, 2010)
Energetic materials have a wide variety of industrial, civil, and military applications. They include a number of organic compounds such as RDX (1,3,5- trinitroheahydro-s-triazine), HMX (octahydro-1,3,5,7-tetranitro-l ,3,5,7-tetrazocine), DAAF (3,3'-diamino-4,4'-azoxyfurazan), DAATO35 (3,3'-azobis(6-amino-l,2,4,5- tetrazine)-mixed N-oxides), etc. These materials release huge chemical energy during their decomposition. The decomposition of energetic materials is initiated with a shock or compression wave or a spark. Such events in solids generate molecules in the excited electronic states. Hence, in order to maximize release of the stored chemical energy in the most efficient and useful manner and to design new energetic materials, the unimolecular decomposition mechanisms and dynamics from excited electronic states should be understood for these systems. This thesis describes understanding about unimolecular decomposition of energetic materials from their excited electronic states. A few fundamental questions at molecular level dealing with electronic excitation of energetic materials are addressed here: (a) what happens immediately after electronic excitation of energetic molecules?; (b) how is excess energy partitioned among product molecules following electronic excitation?; (b) what are the mechanism and dynamics of molecular decomposition?; (d) does nonadiabatic chemistry (a process that span multiple electronic potential energy surfaces) through conical intersection (crossing of different potential energy surfaces) dominate system behavior? Both energy and time resolved spectroscopic techniques are used in this effort. The product internal state (rotational and vibrational) distributions are probed using mass and energy resolved spectroscopic techniques using time-of-flight mass spectrometry (TOFMS) and laser induced fluorescence (LIF) spectroscopy. Analyzing the product internal state distributions, the mechanisms of unimolecular decomposition of energetic molecules from excited electronic states are determined. The femtosecond pump-probe spectroscopic technique is utilized to determine ultrafast decomposition dynamics of these molecules. From a theoretical point of view, multiconfigurational methodologies such as, CASSCF and CASMP2 are used to model the processes involving excited electronic states of energetic molecules. Influence of nonadiabatic chemistry in the overall decomposition of energetic molecules is also theoretically judged. The primary energetic systems whose nonadiabatic chemistry discussed here are the nitramine (e.g., RDX, HMX), furazan (e.g., DAAF), and tetrazine-N-oxide (e.g., DAATO3.5) based energetic species. A number of model systems, which are simple analogue molecules of the large and more complex energetic materials, are studied in detail to understand nonadiabatic energetic behavior of a single energetic moiety of particular class. Subsequently, the decomposition mechanism for more complex energetic systems are studied and compared with that of their model systems. Nitramine energetic materials and model systems undergo nitro-nitrite isomerization followed by IV NO elimination. Nitramine energetic materials dissociates in the ground state generating rotationally cold (20 K) distribution of the NO product. Nitramine model systems dissociates in the excited state surface producing rotationally hot (-120 K) distribution of the NO product. The nitro-nitrite isomerization happens through conical intersection. Furazan based model molecules (e.g., furazan) possess two different pathways of decomposition: ring contraction and ring opening. These two pathways are electronically nonadiabatic. The ring contraction mechanism generates rotationally cold (20 K) product NO and the ring opening mechanism generates rotationally hot (100 K) product NO. Furazan based energetic material (DAAF), however, dissociates only through a ring contraction mechanism. Thus nonadiabatic pathways control the decomposition of furazan based molecules. Decomposition of tetrazine-2,4-dioxide based molecules involves a ring contraction mechanism through (Si/So)ci, producing only rotationally cold (20 K) but vibrationally hot (1200 K) distributions of the NO product. Tetrazine-l,4-dioxde undergoes similar decomposition pathway through (Si/So)ci; however, it produces rotationally hotter (50 K) but vibrationally colder distribution of the NO product. Thus the relative position of the oxygen atoms attached to the tetrazine ring is important parameter along with their nonadiabatic chemistry controlling their final energetic reactivity. Decomposition dynamics of all energetic materials is faster than 180 fs. Considering the influence of conical intersections in the excited electronic state decomposition of energetic materials, rotationally cold N2 product is predicted to be the major decomposition product of high nitrogen content energetic species. The present work infers that generation of internally cold product is an important characteristics of a true energetic molecule. Presence of low lying chemically relevant conical intersections provides a direct pathway of ultrafast decomposition chemistry of energetic molecules. The energy barrier to the low lying chemically relevant conical intersection, in principle, would be a point of interest to make a system more or less energetic.
Covers not scanned.
Keywords: Excited state chemistry; Decomposition (Chemistry); Bioactive compounds